Islam and Local Wisdom in Indonesia - Dinar Fatmawati (Journal of Social Science, 2021)
Local wisdom is knowledge that can be from the local community that applies to a particular area and will be different from one area to another in the way it applies. Local wisdom is evidence of an existence of the behavior of local people who show the color of behaviors that contain values, norms, customs, have a wise nature, wise, and good value. mutually agreed upon in a particular place.